2004
DOI: 10.1021/bi049111r
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues of the IFNAR1 Chain of the Type I Human Interferon Receptor Critical for Ligand Binding and Biological Activity

Abstract: The antiviral and antiproliferative activities of human type I interferons (IFNs) are mediated by two transmembrane receptor subunits, IFNAR1 and IFNAR2. To elucidate the role of IFNAR1 in IFN binding and the establishment of biological activity, specific residues of IFNAR1 were mutated. Residues (62)FSSLKLNVY(70) of the S5-S6 loop of the N-terminal subdomain of IFNAR1 and tryptophan-129 of the second subdomain of IFNAR1 were shown to be crucial for IFN-alpha binding and signaling and establishment of biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 48 publications
(65 reference statements)
1
38
0
Order By: Relevance
“…2A), with a stronger signal for IFNAR2. The difference of band intensity was probably due to the higher level of IFNAR2 than IFNAR1 expression in this cell line, as shown on the corresponding whole cell extract (28). A similar experiment with a Jurkat cell line expressing a FLAG-tagged IFNAR1 showed that IFNAR1 was palmitoylated in this human lymphoid cell line also (data not shown).…”
Section: Ifnar1 Endocytosis and Ifn-␣-induced Jak/stat Signalingsupporting
confidence: 58%
See 2 more Smart Citations
“…2A), with a stronger signal for IFNAR2. The difference of band intensity was probably due to the higher level of IFNAR2 than IFNAR1 expression in this cell line, as shown on the corresponding whole cell extract (28). A similar experiment with a Jurkat cell line expressing a FLAG-tagged IFNAR1 showed that IFNAR1 was palmitoylated in this human lymphoid cell line also (data not shown).…”
Section: Ifnar1 Endocytosis and Ifn-␣-induced Jak/stat Signalingsupporting
confidence: 58%
“…Parental Plasmids and Mutagenesis-Wild-type human IFNAR1 was expressed in pEFIREShyg derived from pIREShyg as described previously (28). Mutagenesis of the IFNAR1 receptor chain was performed using the QuickChange site-directed mutagenesis kit (Stratagene, Amsterdam).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the antiviral effect of IKK⑀ requires IFN induction, we then examined its effect on HCV expression in the presence of anti-IFNAR1 antibodies known to compete specifically for the binding of type I IFNs to the IFNAR chain of the IFN receptor. 31,32 Analysis of STAT1 phosphorylation in response to IFN␣ or IFN␥ allowed to determine that the IFN receptor was functional in the HCV replicon cells as in the parental Huh-7 cells (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…For neutralization of IFN-␣ binding, we used a purified preparation of anti-IFNAR1 monoclonal antibody 64G12 as described. 31,32 For the detection of total levels and phosphorylated levels of Stat1, we used polyclonal antibodies anti-Stat1, anti phosphoSTAT1 Ser727, and anti phosphoSTAT1 Tyr701 (Cell Signaling Technology, Danvers, MA). For the detection of flag STAT1␣ Y701F, flag STAT1␣, and flag (IKK⑀wt), we used anti-flag monoclonal antibody (anti-FLAG M2; Sigma, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%